Introducing Structural Snapshots. (1st December 2015) - Wlodawer, Alexander
Abstract : Structural Snapshots are new to The FEBS Journal . For this series of invited contributions, leaders in the field of structural biology are requested to provide a succinct discussion of a particular structure recently published by their laboratory. The Features Editor, Alex Wlodawer, introduces the series.